The efficacy of small interfering RNAs targeted to the type 1 insulin-like growth factor receptor (IGF1R) is influenced by secondary structure in the IGF1R transcript. - Bohula, E; Salisbury, A; Sohail, M; Playford, M; Riedemann, J; Southern, E; Macaulay, V (2003)
The type 1 insulin-like growth factor receptor (IGF1R) is often overexpressed by tumors and mediates growth and apoptosis protection. We previously showed that antisense reagents complementary to the IGF1R translation start site enhance radio- and chemosensitivity and impair Atm function. However these agents induce relatively modest IGF1R down-regulation and affect insulin receptor levels. To identify alternative sites for molecular targeting, we utilized scanning oligonucleotide arrays to probe the secondary structure of IGF1R mRNA. This strategy enabled selection of antisense oligonucleotides that generated high heteroduplex yield with IGF1R but not insulin receptor transcripts. Antisense oligonucleotides that hybridized strongly to IGF1R mRNA caused IGF1R down-regulation within intact tumor cells, whereas weakly hybridizing oligonucleotides were inactive. Furthermore, the ability of small interfering RNAs (siRNAs) to block IGF1R expression correlated with the accessibility of the target sequence within the transcript. Thus, siRNAs corresponding to weakly hybridizing oligonucleotides caused minor IGF1R down-regulation, whereas siRNAs homologous to accessible targets induced profound sequence-specific IGF1R gene silencing, blocked IGF signaling, and enhanced tumor cell radiosensitivity. This indicates that secondary structure in the target transcript has a major effect on siRNA efficacy. These findings have implications for siRNA design and suggest that IGF1R-targeting agents incorporating this mode of action have potential as anticancer therapy.